Melting–Dropping Property of Blast Furnace Charge on the Basis of Its Slag Formation Behavior - Yonghong Wang; Jiang Diao; Bing Xie; Chenglin Qi; Ping Du (Metals, 2022)
In order to reveal the melting–dropping property of a charged blast furnace (BF) and the mechanism of its slag formation, such as the temperature interval of slag formation, the pressure drop during the reduction process, and the K value of each sample, the soft melt drop experiment was tested in a large-capacity melting–dropping furnace. The results show that a positive linear relationship exists between the slag melting behavior and the melting–dropping property of the corresponding charge. The results indicate that owing to their poor melting–dropping property, single iron ores are not suitable for BF production and the charging mix can improve slag formation as well as the melting–dropping property when the temperature is increased. Chemical composition is the key factor that will affect slag formation. An excessive amount of lump ore in the charging mix favors the formation of a high-fusion point slag phase such as spinel at low temperatures. The charging mix containing fewer lump ore has high FeO content in the slag, decreasing fluidity at increased temperature. Consequently, the gas path is choked and permeability is reduced.